Acerca de J. Calvino y su teología sistemática - Moya Bedoya, Juan Diego (2012)
This paper is a synthesis of some of John Calvin's systematic theological tenets. Conspicuous between them is the theological assertion known as double predestination (=praedestinatio gemina). Identically, this paper concerns the preeminence accorded by the Geneva reformer to Holy Writ. Incidentally, it explores the Calvinist concept of faith.